Evaluation of Passive Islanding Detection Methods for Line to Ground Unsymmetrical Fault in Three Phase Microgrid Systems: Microgrid Islanding Detection Method - Bangar Raju, L.; Subba Rao, K. (Engineering, Technology & Applied Science Research, 2021)
Distributed Generators (DGs) are incorporated in the power distribution systems to develop green energies in microgrids. Islanding is a challenging task in a microgrid. Different types of islanding methods, e.g. local and remote methods, have been developed for handling this task, with local methods being easier to implement, while remote methods are communication-based and costly. The local methods are classified as passive, active, and hybrid, out of which the passive methods are more simple and economical. In this paper, a passive islanding detection method is proposed to detect single line to ground fault. This fault is considered to represent the 60 to 70% of the total un-intentional faults of this category. The available passive methods cannot detect islanding at lower power mismatches as the variations in voltage and frequency fall within thresholding values. In this method, the voltage signals are first retrieved at the targeted DG output and then the phase angle is estimated. Finally, the phase angle is differentiated to get Rate Of Change Of Voltage Phase Angle (ROCOVPA) to detect islanding, and then it is compared with the Rate Of Change Of Frequency (ROCOF) at zero percent power mismatch. Simulation results depict that the ROCOVPA is more effective than ROCOF. The proposed method not only reduces detection time and Non-Detection Zone (NDZ) but is also stable during non-islanding cases like load connection and disconnection to avoid nuisance tripping.